SASON REBELS DURING THE REPUBLIC PERIOD AND THE TAKEN - Abdulaziz KARDAŞ (Fırat University, 2019)
The location of Sason, a district of Province of Siirt, comprises very steep mountains and impassable valleys. The public of the region who had a very primitive lifestyle had disobedience against the State beginning from the Constitutional Period. One of the main reasons behind this was the rebellions initiated by the Armenian and some tribes. The disability of the measures taken against them caused such outbreaks continue until the foundation of the Republic. Following the foundation of Republic, the influence and authority of the state started to be settled all around the country in accordance with the founding philosophy of the newly established state. Within this period, rebellions arose around Sason and in the neighborhood. These incidents in the region were quelled with the big efforts of the Government and the military troops, and the people of Sason were sent to Western provinces for residence after prohibiting the area for housing. Based on the experiences from the inefficient measures taken in Sason and around in the past, relevant military and administrative measures were taken accordingly. Thereby, the influence of State was established and public works started in Sason. During the rule of Adnan Menderes government, this punished area was made available for housing again with the cabinet decree dated 1 July 1950 and the lands were returned to their owners with a decree.